Gentzen calculi for modal propositional logic - Poggiolesi, Francesca. 1980-; SpringerLink (Online service). (Dordrecht, Netherlands Springer Dordrecht, 2011)
The book is about Gentzen calculi for (the main systems of) modal logic. It is divided into three parts. In the first part we introduce and discuss the main philosophical ideas related to proof theory, and we try to identify criteria for distinguishing good sequent calculi. In the second part we present  the several attempts made from the 50?s until today to provide modal logic with Gentzen calculi. In the third and and final part we analyse new calculi for modal logics, called tree-hypersequent calculi, which were recently introduced by the author. We show in a precise and clear way the main results that can be proved with and about them
PartI An overview of the sequent calcus -- PartII, Sequent caluli for modal logic -- Part III, Tree-hyperseqent calculi -- Reference -- Symbols and notations -- Index.
Electronic reproduction.
Keywords: Modality (Logic)